Species composition, diversity, and size variation of mushroom corals (Fungiidae) in Gili Noko, Bawean Island, Indonesia - Mudzakky, Fathul Hilmy; Ar Royyan, Muhammad Abyan (Journal of Marine Resources and Coastal Management, 2025)
This study examines the community structure of mushroom corals in the waters of Gili Noko, Bawean Island, Indonesia, focusing on species composition, diversity, dominance, and size variation across three observation stations. Two species were identified: Fungia fungites and Herpolitha limax, with a total of 20 individuals recorded. Fungia fungites was the most dominant, particularly at Station 2, which had the highest abundance (n=8). The Shannon-Wiener diversity index ranged from 0.451 to 0.562, indicating very low species diversity in absolute terms. However, given the naturally limited species richness within mushroom corals, these values suggest a relatively balanced community structure. The dominance index ranged from 0.625 to 0.722, reflecting moderate species dominance, with Fungia fungites being more prevalent but not overwhelmingly so. Polyp size varied across stations, with Fungia fungites reaching the largest average diameter at Station 1 (9.8 cm) and Herpolitha limax at Station 2 (16.3 cm), suggesting that microhabitat conditions, coral density, and sandy-rubble substrate influence growth patterns. The presence of mushroom corals at all stations suggests generally favorable environmental and substrate conditions. These findings highlight the ecological value of Gili Noko’s reef habitat and emphasize the importance of conservation efforts to mitigate potential threats from human activity and climate change. Future research should prioritize temporal monitoring and assessments of anthropogenic pressures to support sustainable reef management in the area.